2021
DOI: 10.1111/ijd.15654
|View full text |Cite
|
Sign up to set email alerts
|

Progress and lack of progress in hyperhidrosis research 2015–2020. A concise systematic review

Abstract: Hyperhidrosis is excessive sweating that is uncontrollable and occurring regardless of temperature. Quality of life is significantly impaired, and psychiatric comorbidity is common.The objective of the study is to undertake a systematic review of research in the last 5 years regarding hyperhidrosis. Five databases were searched from July 2015 to July 2020 for all research on hyperhidrosis. High-quality research articles were sought for progress in diagnosis, etiology and epidemiology, and use of patient report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The disorder is associated with significant impairment in the quality of life of patients who suffer from focal or generalized HH. HH is still an under-researched condition, and progress in the diagnostics, etiology, and treatment of HH is limited [ 6 ]. Because it is a neurologic disorder of the ANS, knowledge on the physiology, anatomic pathways, and diagnostic procedures is necessary to optimize treatment for patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disorder is associated with significant impairment in the quality of life of patients who suffer from focal or generalized HH. HH is still an under-researched condition, and progress in the diagnostics, etiology, and treatment of HH is limited [ 6 ]. Because it is a neurologic disorder of the ANS, knowledge on the physiology, anatomic pathways, and diagnostic procedures is necessary to optimize treatment for patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Kristensen et al concluded that HH is still an underestimated and understudied chronic disorder [6]. The prevalence of HH is estimated at 1.6% in the UK and between 1.0 and 4.8% in the USA [29][30][31].…”
Section: Pathological Sweatingmentioning
confidence: 99%
See 1 more Smart Citation